Elizabeth and Zenobia - Miller, Jessica, 1985- (Amulet Books, 2017)
When timid Elizabeth's father takes her and her fearless friend, Zenobia, to his family home, Zenobia becomes obsessed with finding a ghost there, and then Elizabeth learns she had an aunt who disappeared from the house years ago.